Port and Harbour Networks in Crete during Late Antiquity (4th – mid-7th c. AD): A Modern Approach - Roussos, Konstantinos (Journal of Greek Archaeology, 2021)
Ports and harbours were of paramount importance for past human societies, since they played multiple roles in many different historical periods. In recent decades, port and harbour studies in archaeology have moved towards a social and economic approach, focusing on the localized meanings of these infrastructures as well as on various key topics including human-environmental interaction, material culture, settlement systems, human behavior and action, identity, ideology, communication networks and trade, war and peace, and technological evolution, etc. Especially in the context of the Mediterranean islands, ports and harbours have played vital roles in wider social, economic, and political networks. Crete, which was diachronically a diverse and interactive insular world within the Eastern Mediterranean, offers a fertile ground for investigating meticulously a wide range of key topics related to ports and harbours in Late Antiquity (the 4th – mid-7th centuries AD).